Scientific Note on Blending Leadership Theories for Global Sustainability - Pollard, Jennifer N. (Historia Ambiental Latinoamericana y Caribeña (HALAC) revista de la Solcha, 2025)
This scientific note is from a capstone project for the Masters of Science in Organizational Leadership (MSOL) program at Johns Hopkins University during the Spring 2025 semester of January to May 2025. The goal was to design a holistic training program for leaders of public gardens by balancing the lessons of four MSOL classes with Eastern leadership philosophies for the purpose of meeting the goals of the 2030 Agenda for Sustainable Development. Paul Smith, Secretary General of Botanic Garden Conservation International (BGCI) stated in 2024, “Botanic gardens are complex organisations, and their leaders need to acquire a wide range of skills and experience if they are to lead gardens effectively”.1 By embracing leadership methodologies that blend traditional leadership theories from the West with less mainstream theories from the East, this approach can offer an alternative that understands and acknowledges the lessons and limitations of both, providing garden leaders with a wide range of skills. The result is a practical, holistic, and sustainable approach that gives leaders of public gardens a versatile advantage in how to lead our world to a healthy and sustainable future.